Chronic pain: psychological formulation and MDT working: a COVID-19 pandemic reflective update. Issue 9 (September 2022) - Robinson, Louise; Fox, Amy
Abstract: Chronic pain management is complex and often a challenge to manage. Patients' expectations are frequently at odds with the treatment outcomes which can be a significant source of distress. This is been further compounded by the significant impact of the coronavirus disease (COVID-19) pandemic with patients' access to pain clinic services reduced in many areas. Clinical psychologists work as part of the multidisciplinary pain team to draw together information and develop a biopsychosocial understanding of how to support patients to live well while experiencing ongoing pain in the context of the COVID-19 pandemic. This article presents two alternative models for formulating and providing therapy for individuals experiencing chronic pain including consideration of the impact of the COVID-19 pandemic: cognitive behavioural therapy and acceptance and commitment therapy. Psychologically informed strategies to support healthcare professionals in their interactions with people with chronic pain are presented.